Fabrication of Nanostructured TiO2 Using a Solvothermal Reaction for Lithium-ion Batteries - Jicai Liang; Ziyi Wang; Zhisen Li; Xiaofeng Wang; Kaifeng Yu (Nanomaterials and Nanotechnology)
Nanostructured TiO2 was successfully synthesized via a facile one-pot solvothermal reaction followed by calcina‐ tion. Hydrolysis and polycondensation of titanium butox‐ ide (Ti(OR)4) were performed in the presence of sodium dodecylbenzenesulfonate (SDBS). The morphologies, crystallinity and compositions of obtained samples were identified by the methods of X-ray diffraction (XRD), Brunauer–Emmett–Teller (BET) and transmission electron microscopy (TEM). It was found that the nanostructured TiO2 with an average diameter of 10±5 nm had the crystal type of anatase. A good specific surface was also obtained by the standard multipoint BET method (119.2 m2/g). As the anode materials for the lithium-ion batteries (LIBs), the anatase phase TiO2 demonstrated a relatively high gravi‐ metric specific capacity of 264.8 mAh g-1. The reversible capacity of TiO2 remained 196.4 mAh g-1 at a rate of 0.2 ̊C after 100 cycles. It indicated that this kind of TiO2 possessed a good electrochemical performance.